2010
DOI: 10.1039/b907301a
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembled monolayers of thiols and dithiols on gold: new challenges for a well-known system

Abstract: Self-assembled monolayers (SAMs) of alkanethiols and dialkanethiols on gold are key elements for building many systems and devices with applications in the wide field of nanotechnology. Despite the progress made in the knowledge of these fascinating two-dimensional molecular systems, there are still several "hot topics" that deserve special attention in order to understand and to control their physical and chemistry properties at the molecular level. This critical review focuses on some of these topics, includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

70
1,429
8
41

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,281 publications
(1,548 citation statements)
references
References 353 publications
(616 reference statements)
70
1,429
8
41
Order By: Relevance
“…3) and the X-ray photoelectron spectroscopy (XPS) data ( Supplementary Fig. 4) of the resulting product after purification confirmed that the oleylamine was exchanged by ODT, which was in agreement with the previous report 30 .…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…3) and the X-ray photoelectron spectroscopy (XPS) data ( Supplementary Fig. 4) of the resulting product after purification confirmed that the oleylamine was exchanged by ODT, which was in agreement with the previous report 30 .…”
Section: Resultssupporting
confidence: 80%
“…The effects of thiols and other sulfur-containing species (for example, sulfur (S) and H 2 S) on the surface structure of metals have been studied previously 30,[32][33][34] . It has been well documented that thiol molecules can induce surface reconstruction of gold films, for example, Au(111), due to the spontaneous formation of Au-S covalent bond 30,[35][36][37] .…”
Section: Resultsmentioning
confidence: 99%
“…As stated earlier, the packing density of SAMs increases with chain length 26 , thereby a monotonic increase in loading capacity is expected for np-Au surfaces modified with amino-thiol SAMs of increasing chain length. However, as the packing density increases, the alkanethiols become more brush-like and extend further away from the surface.…”
mentioning
confidence: 81%
“…Common characterization techniques for SAMs include grazing incidence angle IR spectroscopy, X‐ray photoelectron spectroscopy, scanning tunneling microscopy, and atomic force microscopy 7. SERS gives more localized, molecular information than grazing angle IR spectroscopy, whereas in the future, the combination with atomic force microscopy in tip‐enhanced Raman spectroscopy is expected to go to the extreme of combining both molecular information and nanoscale resolution 8.…”
mentioning
confidence: 99%